Factors Affecting Strategy Implementation: Communication, Commitment, and Consensus - Afif Maulana Ibrahim; Hapzi Ali (Greenation Research & Yayasan Global Resarch National, 2024)
In the ever-evolving landscape of contemporary business, successful strategy implementation remains a formidable challenge for organizations. Bridging the gap between strategy formulation and execution is vital for sustainable success, with communication, commitment, and consensus emerging as pivotal elements influencing this process. This journal article explores the intricate relationships between communication, commitment, and consensus in the context of strategy implementation. Employing the research library method, this article systematically reviews and analyzes literature from diverse sources, offering a comprehensive understanding of the factors influencing strategy implementation. The research library method enables a thorough exploration of the nuanced relationships between communication, commitment, and consensus. The article concludes by formulating hypotheses for further research: (1) Communication affects Strategy Implementation; (2) Commitment affects Strategy Implementation; (3) Consensus affects Strategy Implementation. Acknowledging the importance of these factors is crucial for organizations aiming to achieve strategic goals and long-term success in a rapidly evolving business landscape